Metamorphosis / Muhammad Khalik Mustafa - Mustafa, Muhammad Khalik (Universiti Teknologi MARA, Perak, 2021)
The word metamorphosis representing the meaning the process of transformation, alteration, change and rebirth. Metamorphosis is an idea inspired from the adaptation of traditional Malay male attire which is transformed into a more casual and fashionable attire as well as wearable for any occasions. This contemporary design of traditional Malay male attire provides a phenomenon as it goes together with the current fashion development in the world of globalization. The main aim of this study is to explore, examine and analyze the nature of Malay clothes. This study also describes the existence of type of dresses, the way they are used and sensitivity to clothes received as a heritage of Malay culture. As stated by Siti Zainon Ismail (2004) since the 15th century AD, there is the concept of clothing, "wearing the Malay way" recorded in old Malay literary texts in "Hikayat Hang Tuah". The writing is viewed as a cultural record of clothing, how it is used and elements of traditional values and norms in the Malay culture. Objective for this product is to transform the traditional style of Malay male attire to a "new look" by following the current fashion trend. Every piece of the design plays with the characters and the uniqueness of this traditional attire which is persistently inscribed in the Malay history books such as kekek, pesak, cekak musang, tulang belut and many more. The wearing of traditional Malay male attire can be seen nowadays only in certain events and occasions. Among the attire studied here are baju Kurung teluk belanga, baju sikap, baju kehormatan Barat, baju takwa, and baju kurung cekak musang. These original designs are given a new twist or in other word, new fashion trends. The usage of stripes and checker patterns gives life and reminisce the memory the once loved age-old patterns. The softer denim fabric is used to give it a trendier effect instead of the usually used fabrics. It can be concluded that what modernization have done on this traditional attire to be as a casual wear for Malaysian men is acceptable.